Empowering leadership and team creativity: Understanding the direct-indirect path - Ahmad Adeel; Samreen Batool; Rizwan Ali (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
This study investigated the relationship between empowering leadership and team creativity by integrating the theory of group behavior with componential theory of creativity. For this study, data was collected from two sources (343 Subordinates, 67 Supervisors) by temporally dividing data collection process into two points in time for independent, dependent, and mediating variables from employees of a bank operating in Pakistan. Random coefficient analysis technique was used with Mplus 7.0 to analyze nested data for preliminary analysis and analysis of mediation and indirect effects. Mediation was analyzed using the indirect effect of random models and further confirmed the confidence using bootstrapping procedure. Through this study, the researchers tried to explore the inconsistent relationship between empowering leadership behavior and team creativity. It was found that empowering leadership behavior affects the team level creativity of employees directly and indirectly through the mediation of team learning behavior and team psychological empowerment as team process and team emergent states respectively. The results indicated that empowering leadership enhances the learning potential of teams and team empowerment perception which in turn enhances team level creativity. Further research findings, implications, and future research directions also discussed in this research.
Keywords: M54; J2; C92; 650; empowering leadership; team learning behavior; psychological empowerment; team creativity